Thromboembolic and bleeding complications after elective cardioversion of atrial fibrillation : a nationwide cohort study - Itäinen-Strömberg, Saga; Lehto, Mika; Halminen, Olli; Putaala, Jukka; Haukka, Jari; Lehtonen, Ossi; Teppo, Konsta; Mustonen, Pirjo; Linna, Miika; Hartikainen, Juha; Airaksinen; Kari Eino Juhani; et al. (Oxford University Press, 2025)
Aims: Elective cardioversion (ECV) is routinely used in atrial fibrillation (AF) to restore sinus rhythm. However, it includes a risk of thromboembolism even during adequate oral anticoagulation treatment. The aim of this study was to evaluate the risk of thromboembolic and bleeding complications after ECV in a real-life setting utilizing data from a large AF population.
Methods and results: This nationwide register-based study included all (n = 9625) Finnish AF patients undergoing their first-ever ECV between 2012 and 2018. The thromboembolic and bleeding complications within 30 days after ECV were analysed. The mean age of the patients was 67.7 ± 9.9 years, 61.2% were men, and the mean CHA2DS2-VASc score was 2.6 ± 1.6. Warfarin was used in 6245 (64.9%) and non-vitamin K oral anticoagulants (NOACs) in 3380 (35.1%) cardioversions. Fifty-two (0.5%) thromboembolic complications occurred, of which 62% were ischaemic strokes, 25% transient ischaemic attacks, and 13% other systemic embolisms. Thromboembolic events occurred in 14 (0.4%) NOAC-treated patients and in 38 (0.6%) warfarin-treated patients (odds ratio 0.77; confidence interval: 0.42-1.39). The median time from ECV to the thromboembolic event was 2 days, and 78% of the events occurred within 10 days. Age and alcohol abuse were significant predictors of thromboembolic events. Among warfarin users, thromboembolic complications were more common with international normalized ratio (INR) <2.5 than INR ≥2.5 (0.9% vs. 0.4%, P = 0.026). Overall, 27 (0.3%) bleeding events occurred.
Conclusion: The rate of thromboembolic and bleeding complications related to ECV was low without significant difference between NOAC- and warfarin-treated patients. With warfarin, INR ≥2.5 at the time of cardioversion reduced the risk of thromboembolic complications.